A Taxonomic Account of Commelinaceae Subtribe Cyanotinae in Thailand - Boonsuk, Boonchuang; Chantaranothai, Pranom; Kantachot, Chortip (Tropical Natural History, 2023)
Commelinceae subtribe Cyanotinae, which contains one species of Belosynapsis Hassk. and five species of Cyanotis D. Don in Thailand, are described based on morphological data. Keys to the genera and species are presented. Morphological descriptions of both genera are provided, as well as information on each species' distribution, ecology, conservation status, vernacular names, and additional notes. Cyanotis barbata D. Don, Tradescantia ciliata Blume, and T. capitata Blume have also been lectotypified.